Learning strategy for the formation of tactical thinking in wrestling athletes, category 11-12 years - Martínez-Saravia, N. D.; Laínez-Bonilla, A.; Laínez-Bonilla, J. E.; Sánchez-Ramírez, L. D. L. C. (Journal of Human Sport & Exercise, 2020)
Sports activities are essentially complex and require great muscular and mental tensions, therefore, they must be performed by the athlete in a conscious way and this is possible due to the participation of psychological processes, especially thought, which is linked to all sports performance. However, it is currently the least treated from a didactic-methodological approach in wrestling sport. The research was carried out with the purpose of applying a learning strategy for the formation of tactical thinking, which allows the satisfactory execution of tactical actions in situations during the combat of wrestling athletes in the 11-12 year category. The sample was made up of 10 athletes, 15 sports educators and three managers (methodologists at the provincial and national level). Cronbach's Alpha (Internal Consistency Index) was used, determining the reliability of the applied instruments. The research consists of three phases for its development: the first for the determination of the current state of the formation of tactical thinking, from the dimensions and indicators expressed in an individual worksheet; in the second the learning strategy is applied; and in the third, the applicability of the strategy was corroborated through statistical techniques in the comparison before and after its use.